Reliability performance in distribution system based on the amount of power supply by generators and synchronous compensators in the system - Noor Fatin Farhanie, Mohd Fauzi; Nur Nabihah Rusyda, Roslan; Mohd Ikhwan, Muhammad Ridzuan (Springer Science and Business Media Deutschland GmbH, 2022)
One of the main aspects in power quality is the reliability in power system. Reliability is known as the continuous supply of the electricity to the consumers. People depend mainly on the electricity in order to continue in their daily life. The performance of reliability can be evaluated by these three main reliability indices which are System Average Interruption Frequency Index (SAIFI), System Average Interruption Duration Index (SAIDI) and Customer Average Interruption Duration Index (CAIDI). The interrupted of the electricity is due to any failure in the network system and inadequate of the power supplied to the system. In power system, the electricity is supplied to the load by generators which supply both real power and reactive power. Other than generators supply the power, the presence of synchronous compensator also is very important as it stabilize the system. This synchronous compensator is only supplies the reactive power to the system. Since, the failure of the reactive power sources rarely considered. Hence, in this paper the amount of power for both reactive power and reactive power are analyzed to observe the effect to the reliability performance in the network.